Entre a escola unitária e a mercadológica: a trajetória para o mundo do trabalho dos egressos das EEEPS do Ceará - Marques, Daniele Luciano (2016)
The current research discuss the High School program integrated for the Vocational Education of the State School from Ceará which emerged in 2008 through the partnership between the State Government and Federal Government according to Brazil Professionalized Program. The aim was to get aware about the graduate experiences in terms of the labor market, especially the experiences during the curricular internship and post-training. We refer to authors that deal with contradictions of the labor world, to the Vocational Education and those who approach the Unity School such as: Marx (2010;1890), Mészáros (2008;2002), Kuenzer (1991;2005;2011), Saviani (2008;2007), Antunes (1998;2015;2007), Alves (2011), Frigotto (2010;1995), Cunha (2000), Ramos (2011), Ciavatta (2012), Gramsci (1989) and other scholars who contributed to the theoretical field and the analysis of the findings results. It is worth to emphasize that the philosophical analyze in this exploratory research was anchored in the unitary school of Gramsci that proposes a training beyond the interests of workforce to the capital. The datas were collected from legal documents that characterize and guide the object of study, State Schools of Ceará Vocational Education, and through questionnaire with thirty graduates. Along this study, we identified that those ones motivated by getting a technical education as a mean to "minimize" the effects of unemployment and according to the competence pedagogies that guide young apprentice to search for employability, showed mostly that expectations related to training in EEEPs were fulfilled. Although many of the students are working and continuing the distinct area in studies for which they were trained, they said it was an opportunity for personal and professional growth as well as the kickstart for long walk in the labor world. However, other graduates in a fewer number revealed that there was deficiency in forming the EEEPs mainly with regard to the course stage, because the activity does not prevailed directly in the area of the course formation as well as there were some activities related to administrative issues and simple tasks at the companies which granted the internship. Thus, they fulfilled this curricular component of an inconsistent manner with the legal plan established for integrated training. The path to the education of the working class runs through the waves of offers and reaches the commitment of an education beyond economistic limitations of the labor market.